Transitioning to Success: The Link between E-CTE and College Preparation for Students with Learning Disabilities in the United States - Jay S. Plasman; Filiz Oskay; Michael Gottfried (MDPI AG, 2024)
In recent years, there has been a specific call to not only increase the number of engineering-trained individuals but also to address the lack of diversity in science, technology, engineering and mathematics (STEM) fields, including individuals with disabilities. In particular, students with learning disabilities (SWLDs) make up a large portion of all students and are, therefore, a crucial population on which to focus educational and career progression efforts. One potential means of promoting persistence along the STEM pipeline-engineering specifically-is through engineering career and technical education (E-CTE) coursework in high school. Using a nationally representative dataset, we explore how E-CTE participation links to college preparation and transition activities for SWLDs, including math SAT performance, dual credit course participation, college application, and FAFSA completion. Under our more rigorous school fixed-effects models, we find that E-CTE participation is associated with beneficial results across each of our outcomes. The implications are discussed.